Sex Associations Between Air Pollution and Estimated Atherosclerotic Cardiovascular Disease Risk Determination - Alexandre Vallée (Frontiers Media S.A., 2023)
Objective: The purpose of this study was to investigate the sex correlations of particulate matters (PM2.5, PM10, PM2.5-10), NO2 and NOx with ASCVD risk in the UK Biobank population.Methods: Among 285,045 participants, pollutants were assessed and correlations between ASCVD risk were stratified by sex and estimated using multiple linear and logistic regressions adjusted for length of time at residence, education, income, physical activity, Townsend deprivation, alcohol, smocking pack years, BMI and rural/urban zone.Results: Males presented higher ASCVD risk than females (8.63% vs. 2.65%, p < 0.001). In males PM2.5, PM10, NO2, and NOx each were associated with an increased ASCVD risk >7.5% in the adjusted logistic models, with ORs [95% CI] for a 10 μg/m3 increase were 2.17 [1.87-2.52], 1.15 [1.06-1.24], 1.06 [1.04-1.08] and 1.05 [1.04-1.06], respectively. In females, the ORs for a 10 μg/m3 increase were 1.55 [1.19-2.05], 1.22 [1.06-1.42], 1.07 [1.03-1.10], and 1.04 [1.02-1.05], respectively. No association was observed in both sexes between ASCVD risk and PM2.5-10.Conclusion: Our findings may suggest the possible actions of air pollutants on ASCVD risk.